Growing-finishing performance and carcass yield of pigs reared in a climate-controlled and uncontrolled environment - Berton, Mariana Piatto [UNESP]; Dourado, Rita de Cassia [UNESP]; Fernandes de Lima, Flavia Biondi [UNESP]; Bertoncello Rodrigues, Ana Beatriz [UNESP]; Ferrari, Fabio Borba [UNESP]; Carmo Vieira, Leonardo Dimas do [UNESP]; Souza, Pedro Alves de [UNESP]; Borba, Hirasilva [UNESP] (Springer, 2015)
The objective of this study was to evaluate the effect of temperature on the performance and carcass yield of pigs housed in different environments. Twenty castrated male pigs of the Topigs line were assigned to two treatments: T1, controlled environment, and T2, uncontrolled environment containing a shallow pool. A completely randomized design consisting of two treatments and ten repetitions each was used. The data were submitted to analysis of variance, and means were compared by the Tukey test at a level of significance of 5 % using the SAS 9.2 program (SAS Institute, Inc., NC, USA). The results showed that rearing pigs in an uncontrolled environment during the growing and finishing phases reduced daily feed intake (1.722 and 3.164 kg, respectively) and improved feed conversion (2.15 and 2.70 kg, respectively), but did not influence the carcass yield of the animals. In conclusion, rearing pigs under different environmental conditions during the growing and finishing phases influenced animal performance without interfering with carcass yield.
Keywords: Environment; Loin eye area; Feed conversion; Thermoneutrality